The Effect of Environmental Social Governance (ESG) Disclosure on Firm Value with Profitability and Firm Size as Moderation Variables - Adhia, Lusy Laila; Paramita, Veronika Santi (Indonesian Scientific Publication, 2025)
Global warming occurs due to greenhouse gas emissions and carbon emissions that impact climate change, the environment, social life, and the economy. The banking sub-sector plays an important role in sustainability. However, several banks provide financing to firms that are indicated to damage the environment so that they can reduce the firm's value. The value of firms in the banking sub-sector for the 2019-2023 period has decreased. This study looks at how firm value is affected by environmental, social, and governance (ESG), with firm size and profitability as moderating factors. Quantitative method with descriptive and causal approaches. Secondary data sources were obtained from financial statements and sustainability reports. The population includes 47 banks listed on the IDX 2019-2023, with 16 companies as samples, which were selected using purposive sampling. Then statistical analysis tools, such as MRA and panel data regression, were used to analyze the data. The findings show ESG has an adverse impact on firm value. Return on assets cannot reduce the effect of ESG disclosure on firm value. Firm size can enhance the effect of ESG disclosure on firm value.